"Free" Public Universities: Too Much of a Good Thing? - Estrella, Mateo (International Higher Education, 2011)
Many observers would envy Ecuador's public universities, following adoption of a new governing law and the 2008 Constitution, which abolished all student fees. But its 25 public universities are in the odd position of getting too much of a good thing. Elsewhere, advocates for public universities lament a trend toward marketization and privatization and decry shrunken financial contributions from government. Higher education in Ecuador is about to find out if the recent reforms could be problematic, as strings tighten that have just been attached to universities under a bold experiment. There is a particular worry about the threat to university autonomy.